2020
DOI: 10.1016/j.chaos.2020.109924
|View full text |Cite
|
Sign up to set email alerts
|

Forecast and evaluation of COVID-19 spreading in USA with reduced-space Gaussian process regression

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 21 publications
(23 reference statements)
0
49
0
1
Order By: Relevance
“…This could be explained by the heterogeneity of the clusters (countries) included in the model, with different pandemic start date, different socioeconomic characteristics, and public health and political actions against the pandemic; therefore, this produces potentially an overlap of multiple normal distributions curves. This also could be true for large countries with independent states such as USA (implementing multiple political actions and public health strategies at different moments) [ 23 ]. However, for more homogenous clusters (such as New Zealand, Australia, and some Asian countries), the predicted curves were accurate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be explained by the heterogeneity of the clusters (countries) included in the model, with different pandemic start date, different socioeconomic characteristics, and public health and political actions against the pandemic; therefore, this produces potentially an overlap of multiple normal distributions curves. This also could be true for large countries with independent states such as USA (implementing multiple political actions and public health strategies at different moments) [ 23 ]. However, for more homogenous clusters (such as New Zealand, Australia, and some Asian countries), the predicted curves were accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported behavior predictions for the COVID-19 pandemic; most of them focus on specific countries, such as China [ 24 ], Chile [ 25 ], Italy [ 24 ], France [ 24 ], and USA [ 23 , 26 ]. The estimation of end date varies from May 12 (for Chile) to June 15 (for Italy), these dates from more complex models (most of them from a SIR model) are consistent with our predictions for those countries ( Table 1 ), suggestion an acceptable accuracy to describe the epidemic dynamics with a simpler model.…”
Section: Discussionmentioning
confidence: 99%
“…In statistic, regression methods is a set of statistical modeling to forecast the link between a dependent variable and independent variable (s) (Cook andWeisberg 1982, Freedman 2009). As a power tool to forecast the pandemic, various regression methods have been addressed by researchers against COVID-19 (Almeshal, Almazrouee et al 2020, Ji, Zhang et al 2020, Ribeiro, da Silva et al 2020, Sujath, Chatterjee et al 2020, Velásquez, Lara et al 2020.…”
Section: Regression Methodsmentioning
confidence: 99%
“…The incorporation between reduced-space Gaussian process regression and chaotic Bayesian approach to predict the cases of COVID-19 and deaths in USA was presented by ( Arias Velásquez and Mejía Lara, 2020 ). The prevalence of the outbreak was expected to dramatically increase and thus new restricted quarantine actions should be implemented.…”
Section: Introductionmentioning
confidence: 99%